THE INFLUENCE OF CULTURE AND FAMILY TOWARDS THE DECISION TO PURSUE STUDY ABROAD: A CASE STUDY OF MALAYSIAN PUBLIC UNIVERSITIES - Irma Wani Othm, Muhamad Safuan Yusoff , Romzi Ationg ,Mohd Sohaimi Esa , Mohd Kamal Mohd Shah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The choice of educational destination is an active process by individuals, yet it is greatly socially determined by family or friends. This article is to provide an in-depth understanding of how a group of international students managed to be influenced by their families in their decision to study abroad. A qualitative approach was used in this research whereby four public universities of Malaysia had been selected according to the type of universities and location of the research. A group of international students have been interviewed successfully using a set of interview questions which was drafted through a thorough protocol interview which was done during a pilot study. The used of semi structure interview had proven effective to the researchers because researchers had the freedom to interview thoroughly without being fully bound with interview questions that had been constructed. This brought to an even deeper answers exploration related to the problems answered by the respondents. Findings of this qualitative research which is gathered from 40 international students have shown discussion of diaspora-driven motivations on family influence in decision-making to pursue further studies abroad. Based on the discussion in this article, cultural themes are also associated with issues such as opportunities for travel and opportunities for local culture. On the other hand, the uniqueness of cultural diversity in Malaysia has added value to the trust of families and international students in the process of assimilation in a new environment that is different from their home country. Thus, the culture of the institutions of higher learning conducive to the country's initiative to make Malaysia a hub for education in the Asian region. While the categorization of themes such as (i) gaining new experience while in the host country, (ii) assimilating into campus culture and (iii) having the opportunity to gain meaningful experiences in the outside world and (iv) the importance of opinions from family and close friends generated the dominant themes as a result of the research.